2021
DOI: 10.11604/pamj.2021.39.165.24767
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of benign prostate hyperplasia in Nigeria: open prostatectomy versus transurethral resection of the prostate

Abstract: Introduction transvesical (open) prostatectomy (OP), an invasive surgical procedure, is a common form of treatment offered to patients with benign prostatic enlargement in emerging economies. Recently, there has been an increase in the use of electrosurgical means in treating benign prostate hyperplasia in our environment, especially transurethral resection of the prostate (TURP). This study compares the perioperative, short-term outcomes and complications of open prostatectomy and TURP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…This result, which shows an age greater than 50 years, is in line with that reported by MAHAMAT in his study in N'DJAMERA, who reported an average age of 53.54 years [1]. Other authors such as DIAKITE [6] in MALI and OFOHA [7] in NIGERIA reported an average age of 62 and 63.8 years respectively. However, cases of patients under 50 years of age were reported by COULIBALY and colleagues in Côte d'Ivoire in their study of prostatic adenomectomy in twins [8].…”
Section: Discussionsupporting
confidence: 90%
“…This result, which shows an age greater than 50 years, is in line with that reported by MAHAMAT in his study in N'DJAMERA, who reported an average age of 53.54 years [1]. Other authors such as DIAKITE [6] in MALI and OFOHA [7] in NIGERIA reported an average age of 62 and 63.8 years respectively. However, cases of patients under 50 years of age were reported by COULIBALY and colleagues in Côte d'Ivoire in their study of prostatic adenomectomy in twins [8].…”
Section: Discussionsupporting
confidence: 90%
“…The median age of our study sample (68.5 years old) was within the age range reported for open prostatectomy case series from other resourceconstrained settings (63-73 years old) [4,5,9,10]. This finding suggests that older males in resourceconstrained settings, particularly those aged older than 60 years old, might benefit from prostate disease awareness campaigns and prostate disease screening interventions.…”
Section: Gradesupporting
confidence: 70%
“…5 There are many options with minimal invasive surgery but despite all TURP is a procedure of choice. 6 According to a previous study conducted by Chimaobi et al in Nigeria catheter was removed on the first post-operative day with the success rate of 98%. 7 Another study also reported it safe to remove the catheter on the same post-operative day without any major complication.…”
Section: Introductionmentioning
confidence: 99%